Distribution of anopheles mosquitoes and plasmodium knowlesi transmission in Kudat, Sabah Borneo - Ng, Sui Hann (2018)
The zoonotic malaria caused by Plasmodium knowlesi (Pk) threatens the rural residents in Sabah. This disease is transmitted by mosquitoes of genus Anopheles. A study was carried out with the main objective to collect distribution data of Anopheles in Kudat, to investigate whether land use or land cover (LULC) affects the mosquito distribution. Another objective is to examine the parity, proportion of mosquito infected with malaria parasites and estimate longevity of the main vector. Six LULC, namely clearing, forest, rubber, coconut, oil palm plantation and settlement were classified. Mosquito population was sampled from February 2015 to January 2016 in all LULCs. Outdoor human landing catch was performed in 1800-2400 hour to collect exophilic Anopheles. A total of 1,910 individuals, comprised of eight species were collected. The most abundant species was Anopheles ba/abacensis (85%), followed by Anopheles dona/di (6.23%), An. barbumbrosus (3.72%), An. tesse/latus (1.52%), An. maculatus (1.52%), An. barbirostris (1.26%), An. introlatus (0.42%), and An. umbrosus group (0.58%). The highest peak of population was recorded in September 2015, with the peak biting time at 1800-2000 hour throughout the year. Generalized linear mixed model (GLMM) analysis, incorporating negative binomial distribution showed that the number of An. balabacensis collected at clearing (mean 2.98) was significantly lower than coconut (mean 7.12, z-ration=-2.89, p-value=0.045), oil palm plantation (mean 7.13, z=-3.04, p=0.03), forest (mean 7.99, z=-3.25, p=0.01) and settlement (mean 7.70, z=-3.21, p=0.02). Besides LULC, wind speed and rain fall are likely factors to affect mosquito caught. The pattern of mosquito distribution can be described as seasonal. It correlates positively (Kendall tau = 0.867, p < 0.05) to monthly rainfall up to the threshold level of 350mm. All Anopheles collected in Jun 2015 - January 2016 were dissected for the presence of Plasmodium sporozoite in salivary glands and oocytes on midgut wall. As a result, total of 36 individuals of Anopheles balabacensis were infected with malaria parasites, with the highest infection rate (5.45%, n=256) in September 2015. The parity rate of An. balabacensis fluctuated little (54.11±3%) in all LULC throughout the year. The highest entomological inoculation rate (EIR) was 0.14. The longevity of an infective An. balabacensis was estimated 5-6 days. Mosquito controls such as source reduction and fogging to be carried out at 1800-2000 hour are recommended during drought period.